Novos táxons em Apomecynini (Coleoptera, Cerambycidae, Lamiinae) - Martins,Ubirajara R. (2003)
New taxa of Apomecynini (Coleoptera, Cerambycidae, Lamiinae). The following new taxa are described from Brazil: Ischioncha rondonia sp. nov., from Rondônia; Prosenella unicolor sp. nov., from Rio Grande do Sul; Catuaba gen. nov., type species, C. sanguinolenta sp. nov., from Mato Grosso do Sul.